Improving Students' Learning Outcomes in Indonesian Language Subject on Writing Texts of Fantasy Materials Through the Application of Problem Based Learning Learning Models - Irman, Irman (USN Kolaka, 2023)
This study aimed to investigate the effect of the Problem-Based Learning (PBL) model on students’ writing performance and learning outcomes in Indonesian class VIII. The research employed a Classroom Action Research (CAR) design conducted over two cycles with 32 students as participants. Each cycle consisted of planning, implementation, observation, and reflection. Data were collected using student learning outcome tests and analyzed through descriptive quantitative statistical techniques. The findings revealed a progressive improvement in students’ performance: the average score increased from 77 in the first cycle to 82 in the second cycle. Observations indicated that PBL enhanced students’ engagement, collaboration, and ability to apply knowledge to solve problems. Moreover, students demonstrated improved critical thinking and creativity in writing fantasy stories. The results suggest that the PBL model effectively fosters active learning, promotes higher-order thinking skills, and enhances student learning outcomes in Indonesian language education. Implementing PBL encourages collaborative problem-solving, the integration of knowledge and skills, and the application of learning to authentic tasks. These findings provide practical implications for educators seeking to improve student achievement and engagement through innovative instructional strategies.